Logistics service quality and commitment in third party logistics / Harlina Suzana Jaafar and Mohammed Rafiq - Jaafar, Harlina Suzana; Rafiq, Mohammed (Universiti Teknologi MARA Cawangan Pahang, 2005)
This paper proposes a conceptual model aimed at investigating the effects of logistics service quality and relationship quality on commitment in a third party relationship context. It examines customer perceptions of logistics services provided by third party logistics companies. The model incorporates Logistics Service Quality (LSQ) framework (Mentzer et al (2001), which is the recent scale for measuring logistics service quality developed in a single firm in the United States that was rigorously tested. It also explores the causal relationships among the dimensions that make up relationship quality that was previously considered as a global measure and by considering commitment as the critical outcome dimension.